Picromerus bidens (Heteroptera: Pentatomidae) as predator of the Checkerspot Euphydryas aurinia (Lepidoptera: Nymphalidae) - Konvička, Martin; Hula, Vladimir; Fric, Zdenek (Entomologica Fennica, 2005)
The predatory bug Picromerus bidens is reported as a regular predator of the Marsh Fritillary Euphydryas aurinia from the region of western Bohemia, Czech Republic. Adult bugs attack pre-diapause larvae, either exposed or hidden in protective silken webs, and exhibit efficient behaviour, including returning to previously attacked webs. We observed predation in six out of 28 and eleven out of 21 local populations in 2003 and 2004, respectively. In addition, we observed two attacks by nymphs on handicapped adult butterflies. Predation of Melitaeinae by Heteroptera seems to be a widespread phenomenon, and P. bidens can act as a substantial mortality factor in small colonies of E. aurinia.